Cuadro de mando integral en la empresa de servicios ARPAZ CO. - Arteaga , Tito Franklin (2022)
The balanced scorecard is a decision-making management tool. It allows the translation of the organization’s strategy into specific objectives and their evaluation by different indicators. The lack of control indicators in the various perspectives’ limits management capacity in ARPAZ Co. Therefore, applying the balanced scorecard as a management tool is necessary. We started by diagnosing the organizational structure of the company, its processes, and its decision-making. The application stages were defined in terms of financial, customer, process, training, and growth perspectives. Then we proceeded to define the indicators for the key decision-making processes and how to measure the efficiency of the strategies in the organization. Finally, several internal processes were promoted to obtain better results derived from decision[1]making. Based on the deficiencies in business management, improvement actions and strategic objectives aligned with the mission and vision of the organization were achieved.